PENGARUH PERSEPSI PESERTA DIDIK TENTANG KOLEKSI DAN SARANA PERPUSTAKAAN TERHADAP MOTIVASI BERKUNJUNG - Imam Bukhori (STIE Kesuma Negara Blitar, 2015)
The research is an associative research. The chosen population was students of class X and XI of SMK PGRI 2 Malang visiting the school library, that is 223 students. The sampling technique used in the research is simple random sampling with 144 respondents, and the analysis method used is multiple regression method. The result shows that there is a partially positive and significant influence of library collections and facilities on the student visiting motivation to the school library in SMK PGRI 2 Malang. There is a simultaneously positive and significant influence of the library collections and facilities on the student visiting motivation to the school library in SMK PGRI 2 Malang. According to Standardized Coefficients Beta, library facilities have dominant influences on the student visiting motivation to the school library in SMK PGRI 2 Malang. Suggestions that can be recommended related to the result of the research are the school should give more attention in improving the management of the school library facilities focused on the completeness of the library collections and the comfort of the library facilities. As the time to complete the library collections and facilities, students are encouraged to visit the library often. The condition of the student visiting motivation to the school library in SMK PGRI 2 Malang is categorized high enough. That is why, the school is expected to maintain and improve the recent condition. It is intended to improve the student competence as what students are learning. Ways applied by the school recently (like encouraging students to visit the library by including learning program activities taken place in the library) should be maintained. Some strategies are creating a comfortable environment by making the room more colorful and cheerful, providing a set of sound system for music, and spreading the air freshener. About the room design, there are tables of which the color are needed to repaint and it should be added some individual tables, not just group tables. About the ventilation, it should be provided air conditioner (AC). In further researches, it is suggested to take better objects that are other variables of out of the research such as librarians, the headmaster and teachers’ attention, the relationship with the curricula, and programs and activities designed by the librarians. That will probably influence the visiting motivation and the sample used is all libraries in all schools in Malang. Taking all libraries in all schools in Malang, the result of the research will have higher diversities in term of school management that can influence student visiting motivation to the school library. Key Words: Library Collections and Facilities, Visiting Motivation